Overcoming Barriers in Infrastructure Development Planning and Community Involvement - Ainurrohman, Muhammad Alief; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2024)
Abstract. The success of national development is often reflected in infrastructure improvements at the village level, particularly in promoting community welfare. In the specific context, Wunut Village in Porong District, Sidoarjo Regency, faces challenges in infrastructure planning, including transparency issues and limited community participation. The knowledge gap lies in the need for effective infrastructure planning to optimize the use of available resources and to identify obstacles in rural development. This study aims to analyze the village's development planning and identify barriers using a qualitative approach. Based on Syaodih's theory, focusing on achieving better goals, optimizing resources, addressing limitations, and ensuring efficiency, the results show a lack of transparency in the village work plan and passive community participation. This research's novelty highlights the critical role of transparency and engagement in successful infrastructure planning. The implications suggest enhancing community involvement and transparency for more effective rural development. Highlights: Transparency in village government work plans is essential for effective infrastructure development. Community involvement must be improved to enhance the planning and implementation process. Strategic planning is key to overcoming limitations in rural infrastructure projects. Keywords: Infrastructure, Development Planning, Rural Development, Community Participation, Transparency